Prevalence of HIV among blood donors in western region of Libya: comparison between three major western cities before and after Libyan incidences. (مجلة البحوث الأكاديمية, 2018)
Acquired immune deficiency syndrome (Hereafter: AIDS) is a devastating infectious disease caused by the human immunodeficiency virus (HIV). HIV test is one of the obligatory tests on blood donors in Libya and worldwide. The study of the of HIV among blood donors on an area may give a good indication on the prevalence of the virus in the general population on the area. As such, the current study aims to estimate and compare the prevalence of HIV in three major Libyan cities: Tripoli, Misurata and Zleetin, located in the western region of Libya. In addition, it  explores the effect of Libyan incidences in 2011 on the prevalence of the infection. A retrospective study was carried out on 72146 nationwide voluntary blood donors in four blood banks, covering the three cities over a period of four years (2009-2013). Enzyme linked immunosorbent assay (ELISA) was performed to screen blood donors for HIV. Results showed that Misurata has the highest mean prevalence of HIV among the three cities over the period mentioned. The difference in the mean prevalence was statistically significant (P0.05) between Tripoli and Zleetin. The difference in the prevalence before and after the incidences was statistically significant (P0.05) in Zleetin and Tripoli